Questioning Technique as a Conflict Prevention and Resolution Tool - Kertész, Tibor (Interdisciplinary and Child-Friendly Communication, 2025)
This chapter explores the pivotal role of questioning techniques in mediation as both conflict prevention and resolution tools. It emphasises that effective mediation depends not only on asking the “right” questions but on applying a strategic sequence and structure that fosters reflection, empathy, and self awareness. The study highlights the importance of mediators listening attentively to clients’ responses, as answers reveal underlying needs, emotions, and motivations. Through the concept of strategic questioning and “scaffolding,” the text demonstrates how mediators can guide clients – particularly adolescents – towards meaningful participation and empowerment in the process. The chapter analyses various question types, including informational, motivational, reflective, and circular questions, explaining their functions in building understanding and promoting transformative dialogue. By examining both the psychological and methodological dimensions of questioning, this work underlines its significance as a cornerstone of mediator competence and an essential instrument for sustainable, empathetic conflict resolution.Keywords: Strategic Questioning, Mediation, Conflict Resolution, Transformative Mediation, CommunicationTechniques, Empowerment